ANALYSIS OF DATA ON DOSES OF EXTERNAL TERRIGENOUS IRRADIATION OF THE RUSSIAN FEDERATION POPULATION IN MUNICIPAL CONDITIONS - I. P. Stamat; D. V. Kononenko; T. A. Kormanovskaja; N. A. Koroleva (Радиационная гигиена)
By this time in the Russian Federation there is collected a huge file of data describing the influence of all natural sources of ionizing radiation on population in municipal conditions. These data are collected and generalized in radiation hygiene passports of the Russian Federation for the last 16 years and in the reporting forms of federal statistical supervision No 4-DOZ “Data on doses of population irradiation due to the natural and manchanged radiation background” for a period of 14 years. These data are received by direct measurements of gamma radiation dose rate in the premises and in the open air on the territory of settlements. Measurements were made with the most different dosimeters; their technical and metrological parameters differ considerably. In this regard of certain interest is evaluation of this data reliability degree; that will help to find out the reasons of higher levels of the Russian Federation population external irradiation in comparison with average global dose values.In this article an attempt was made to evaluate reliability degree of data on the population external irradiation doses using the radiation hygiene passports of territories and reporting forms No 4-DOZ for the whole period of supervision. For this there was used the known dependence between the gamma radiation dose rate and natural radionuclides effective specific activity (AEFF) in inhabitancy objects. For this purpose there were used the data on average AEFF values of building raw materials and of local manufacture materials, which are presented in radiation hygiene passports of territories. Definition of design value of gamma radiation dose rate in the buildings and in the open air according to AEFF measurement data in building raw materials and in local manufacture materials actually enables to get an independent evaluation of the population external irradiation doses. Comparison of two evaluations of the population external irradiation levels enabled to reveal certain territories on which the population external irradiation doses are obviously overestimated or underestimated. It is proved that the specified population external irradiation dose values for certain entities and for the whole country are much closer to corresponding evaluations by foreign experts and to the average global levels.